Spatial, geographic, and demographic factors associated with adolescent and youth suicide: a systematic review study - Ghadipasha, Masoud; Talaie, Ramin; Mahmoodi, Zohreh; Karimi, Salah Eddin; Forouzesh, Mehdi; Morsalpour, Masoud; Mahdavi, Seyed Amirhosein; Mousavi, Seyed Shahram; Ashrafiesfahani, Shayesteh; Kordrostami, Roya; Dadashzadehasl, Nahid (Frontiers in Psychiatry, 2024)
Background: Suicide is a public health issue and a main cause of mortality among adolescents and the youth worldwide, particularly in developing countries. Objectives: The present research is a systematic review aiming to investigate the spatial, geographical, and demographic factors related to suicide among adolescents and the youth. Methods: In this systematic review, two researchers examined PsycINFO, Web of Science, Scopus, and PubMed databases on December 7th, 2022 with no time limits from the beginning of publication until 2022 to identify the primary studies on spatial and geographic analysis on adolescent and youth suicides. Once duplicate studies were identified and removed, the titles and abstracts of studies were examined and irrelevant studies were also removed. Finally, 22 studies were reviewed based on the inclusion criteria. Results: Our findings show that suicide rates are generally higher among men, residents of rural and less densely populated regions, coastal and mountainous regions, natives, 15-29 age group, less privileged populations with social fragmentation, unemployed, divorced or lonely people, those who live in single parent families, people with mental health issues, and those with low levels of education. Conclusions: Stronger evidence supports the effects of geographic and demographic variables on youth and adolescent suicide rates as compared with spatial variables. These findings suggest that policy makers take spatial and demographic factors into consideration when health systems allocate resources for suicide prevention, and that national policymakers integrate demographic and geographic variables into health service programs.